Layanan Penelusuran Kompleks Berbasis Teknologi Informasi di Perpustakaan - Indah Wijaya Antasari (Al-Ma'mun: Jurnal Kajian Kepustakawanan dan Informasi, 2020)
The purpose of this research is to describe complex search services at the IAIN Purwokerto Library related to information technology, where search uses a search tool in the form of computers and networks. Based on several studies of users in the IAIN Purwokerto library, the library developed its services. Using descriptive method, with a source of complex search service form data in 2017-2019. As a result, the development of information technology is coloring the provision of new services, such as bookless library services, e-library services that can be installed via playstore on android devices, international journal services by subscribing to proquest, etc. Librarians are also required to master technology by providing information technology-based services, in this case complex search services. IT-based complex search services are carried out by integrating all digital services in the library to provide answers to the information needs of users.Keywords: service development, complex search service, digital services, information technology, online search